Organizational Structure and the Limits of Knowledge Sharing: Incentive Conflict and Agency in Car Leasing - Pierce, Lamar (Management Science, 2012)
This paper argues that conflicting incentives among managers may impede potential knowledge-sharing benefits from vertical integration. I study knowledge-based agency costs from vertical integration in car leasing, where manufacturer-owned captive lessors compete with independent lessors. Both organizational forms must acquire and integrate diffuse knowledge to accurately predict vehicle depreciation—a condition critical for profitability. Using a data set of 180,000 leases, I compare contracts of independent and captive lessors across car models, market conditions, and product life cycles. I find that managers in vertically integrated firms have conflicting incentives on whether to accurately and completely share proprietary knowledge, and show that these incentives appear to generate agency costs inconsistent with corporate profitability as managers selectively use and share knowledge for personal gain. The findings suggest that most knowledge benefits of vertical integration will be nullified when managerial interests are incompatible with the profit concerns of the firm. This paper was accepted by Bruno Cassiman, business strategy.